Исследование плавления на границе раздела фаз "шлак - металл" легкоплавких и тугоплавких кусковых добавок - Андриевский, Г.А. (Фундаментальные и прикладные проблемы черной металлургии, 2013)
Разработана математическая модель процессов плавления на границе раздела
фаз «шлак – металл» легкоплавких и тугоплавких кусковых добавок сферической
формы диаметром 25 и 50 мм. В качестве легкоплавкой добавки в расплав рассмотрен ферросилиций марки ФС65, а тугоплавкой – ферротитан марки ФТи30.
Установлено, что плавление куска на границе раздела фаз «шлак – металл» более
продолжительно, чем в глубине металлической ванны независимо от вида ферросплава. Розроблено математичну модель процесів плавлення на межі розділу
фаз « шлак - метал » легкоплавких і тугоплавких кускових добавок сферичної форми діаметром 25 і 50 мм. В якості легкоплавкой добавки в розплав розглянуто феросиліцій марки ФС65 , а тугоплавкої - ферротитан
марки ФТі30. Встановлено, що плавлення шматка на межі розділу фаз
«шлак - метал» більш тривало, ніж у глибині металевої ванни незалежно
від виду феро-сплаву. The aim of this work was to develop a mathematical model and
the study of movement and melting processes at the boundary "slag - metal" for
refractory and easily fusible ferroalloys of spherical shape. Mathematical model of the melting process of ferroalloys in the
melt is developed. It is shown that the duration of ferroalloys melting in melt
depends from the size of their particles, from melt temperature and from molten
bath hydrodynamics. The smelting of ferroalloys in the phase-to-phase "slag -
metal" boundary is longer (approximately twice) than in the metal bath depths.
Ferroalloys thermal properties influence on conditions of melting at the phaseto-phase
boundary "slag - metal are confirmed. Ferrotitanium smelting duration
is longer, than ferrosilicon smelting. The mathematical model for describe the motion and melting
processes of fusible and refractory spherical piece of ferroalloys at the
boundary "slag - metal." is developed.